Carbonized polymer dot with high-temperature-resistant surface activity and solid-state luminescence as well as preparation method and application of carbonized polymer dot

Carbonized polymer dots prepared by hydrothermal reaction method solve the problem of insufficient luminescence performance of carbon dot materials in solid state, achieve high brightness red light emission and high temperature surfactivity, and are suitable for solid state lighting and petroleum industry and other fields.

CN119118107APending Publication Date: 2024-12-13SHANDONG UNIV
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411249641.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-06
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing carbon dot materials have insufficient luminescence performance in solid state, especially poor red light emission performance, and complex preparation process, making it difficult to have high temperature surfactivity and efficient solid state luminescence, which limits its application in the fields of solid state lighting and biological detection.

Method used

Using hydrothermal reaction method, precursors such as rhodamine B, methyl blue or sodium fluorescein were mixed with polyether long-chain polymer and acid, and through hydrothermal reaction and purification, it was prepared to have both high-temperature resistance and solid-state luminescence. The carbonized polymer dots use the structure of polyether long-chain polymer to disperse fluorescent chromophores, resist the aggregation-induced quenching effect, and improve the solid-state luminescence performance.

Benefits of technology

It realizes high-brightness red light emission, improves solid-state quantum yield, ensures biocompatibility, and provides high-performance surfactants and phosphor application solutions for the petroleum industry and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005031890080000011
    Figure HDA0005031890080000011
  • Figure HDA0005031890080000012
    Figure HDA0005031890080000012
  • Figure HDA0005031890080000021
    Figure HDA0005031890080000021
Patent Text Reader

Abstract

The invention provides a carbonized polymer dot with high-temperature-resistant surface activity and solid-state luminescence as well as a preparation method and application of the carbonized polymer dot. The preparation method of the carbonized polymer point with high-temperature-resistant surface activity and solid luminescence comprises the following steps: uniformly mixing a precursor, a polyether long-chain polymer, acid and water, carrying out hydrothermal reaction, and then purifying and freeze-drying to obtain the carbonized polymer point with high-temperature-resistant surface activity and solid luminescence, the precursor is rhodamine B, methyl blue, fluorescein sodium or calcein. The preparation method disclosed by the invention is simple, environment-friendly, cheap and easily available in raw materials, low in cost and high in yield; reaction conditions are easy to realize; the carbonized polymer dot prepared by the invention has both high-temperature-resistant surface activity and solid-state luminescence property, can emit high-brightness red light, has higher solid quantum yield and good biocompatibility, has the capability of serving as commercial fluorescent powder and a surfactant, and has extremely high practical application value in the fields of solid-state illumination, petroleum industry and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a carbonized polymer dot having both high temperature resistant surface activity and solid-state luminescence and a preparation method and application thereof, belonging to the technical field of functional nano material preparation. Background Art

[0002] Carbon dots are a type of luminescent carbon nanoparticles. Due to their excellent optical properties and simple and inexpensive preparation methods, they are considered to be a new type of zero-dimensional carbon nanomaterial with broad application prospects. Unfortunately, carbon dots prepared from small molecule precursors often show aggregation-induced quenching (ACQ) effects similar to organic fluorescent molecules. In the aggregated state, they intensify the collision between molecules and lead to resonance energy transfer or π-π stacking to quench the luminescence. In addition, most of them are prepared by solvent thermal synthesis and have relatively poor water solubility, which greatly limits the application of carbon dots in solid-state lighting and bioassays. The discovery of carbonized polymer dots (CPDs) in 2013 further promoted the development of carbon dot materials. Its cross-linked polymer network structure is one of the effective strategies to achieve non-base-assisted solid-state luminescence of carbon dots. At present, CPDs are an important research idea to achieve solid-state luminescence of carbon dots while retaining the functionality of carbon dots.

[0003] Structurally, by introducing a large steric hindrance on the surface of carbon dots, the approach of the luminescent core can be effectively hindered, thereby achieving the purpose of resisting the ACQ effect. At the same time, appropriate large-sized surface ligands can limit the rotation or vibration of chemical bonds in the chromophore, and the luminescence of carbon dots in the solid state can be further enhanced. In the preparation process of traditional CPDs, small molecule precursors are usually used as raw materials, and different chromophores are doped into the framework structure of CPDs after a polymerization-crosslinking-carbonization process. Not only is the preparation process complicated, but the solid-state luminescence quantum yield and conversion rate of the final product cannot be guaranteed. It is worth mentioning that the preparation of high-brightness red carbon dots is still very difficult, and there are limited precursor polymers that meet the harsh preparation conditions and have both cost and functional advantages. At present, there are few types of red light-emitting CPDs, and long-wavelength emitting CPDs are often quenched in the solid state, and the solution state quantum yield is low.

[0004] In terms of function, the functions of CPDs are currently developed mainly around optical properties, focusing on analysis and detection, lighting, display and other aspects. However, functional CPDs developed based on polymer properties are relatively rare. Among them, amphiphilicity is an important functional branch of polymer material research. However, the research on amphiphilic CPDs is currently in its infancy. In the preparation method of traditional CPDs, the precursor structure is often destroyed after undergoing a high-temperature carbonization process, the advantages of the amphiphilic precursor are greatly weakened, and the surface activity is extremely poor or even disappears. In existing research, amphiphilic carbon dots with better performance are mostly achieved through a two-step method or even a multi-step method, and the preparation process is very complicated.

[0005] Therefore, it is of great significance to develop a carbonized polymer dot with simple preparation method, low cost, high temperature resistant surface activity and efficient solid-state red light emission. Summary of the invention

[0006] In view of the shortcomings of the prior art, the present invention provides a carbonized polymer dot having both high temperature resistant surface activity and solid-state luminescence, and a preparation method and application thereof. The preparation method of the present invention is simple, the reaction conditions are easy to achieve, it is environmentally friendly, the raw materials are cheap and easy to obtain, the cost is low, and the yield is high; the carbonized polymer dot prepared by the present invention has both high temperature resistant surface activity and solid-state luminescence performance, can emit high brightness red light, has a high solid quantum yield, and has good biocompatibility, and has the ability to be used as a commercial phosphor and surfactant, and has extremely high practical application value in the fields of solid-state lighting, petroleum industry, etc.

[0007] In order to achieve the above object, the present invention adopts the following technical scheme:

[0008] A method for preparing carbonized polymer dots having both high temperature resistant surface activity and solid-state luminescence, comprising the steps of:

[0009] The precursor, polyether long-chain polymer, acid and water are mixed evenly, subjected to hydrothermal reaction, and then purified and freeze-dried to obtain carbonized polymer dots with both high temperature resistant surface activity and solid-state luminescence; the precursor is rhodamine B, methyl blue, sodium fluorescein or calcein.

[0010] Preferably, according to the present invention, the polyether long-chain polymer is Pluronic F68, Pluronic L64 or PEG; preferably, the mass average molecular weight of Pluronic F68 is 8000-9000, the mass average molecular weight of Pluronic L64 is 2000-4000, and the mass average molecular weight of PEG is 7000-9000.

[0011] According to the present invention, preferably, the acid is a hydrochloric acid aqueous solution, a sulfuric acid aqueous solution or phosphoric acid; and the mass concentration of the acid is 35-100%.

[0012] Preferably according to the present invention, the mass ratio of the precursor to the polyether long-chain polymer is 1:2 to 1:100, preferably 1:5 to 1:60, more preferably 1:30 to 1:50, and most preferably 1:40.

[0013] Preferably according to the present invention, the mass ratio of the precursor to the volume ratio of the acid is 1:0.1-10 g / mL, preferably 1:0.4-4 g / mL, preferably 1:0.8-0.9 g / mL, and further preferably 1:0.84 g / mL.

[0014] Preferably according to the present invention, the mass ratio of the precursor to the volume of water is 0.001 to 1 g / mL.

[0015] According to the present invention, preferably, the hydrothermal reaction temperature is 170-250°C, preferably 180-240°C, and more preferably 220-230°C.

[0016] According to the preferred embodiment of the present invention, the hydrothermal reaction time is 0.5 to 8 h, preferably 1 to 3 h, and more preferably 1.5 to 2.5 h.

[0017] According to the preferred embodiment of the present invention, the purification method is dialysis; the dialysis time is 4 to 15 days, preferably 5 to 7 days; the molecular weight cutoff of the dialysis bag used for dialysis is X+100 to X+3000Da, wherein X is the mass average molecular weight of the polyether long-chain polymer. The solution to be purified is placed in the dialysis bag, and deionized water is placed outside the dialysis bag.

[0018] A carbonized polymer dot having both high temperature resistant surface activity and solid-state luminescence is prepared by the above method.

[0019] The carbonized polymer dots having both high temperature resistant surface activity and solid-state luminescence are applied in photoluminescent devices, phosphors or as surfactants.

[0020] Preferably according to the present invention, carbonized polymer dots can be compounded with polyether-modified trisiloxane as a surfactant, wherein the mass ratio of carbonized polymer dots to polyether-modified trisiloxane is 1-9:9-1, preferably 5-7:3-5.

[0021] Technical features and beneficial effects of the present invention:

[0022] 1. The preparation mechanism of carbonized polymer dots of the present invention is based on the dehydration condensation between the hydroxyl group at the end of the polyether long-chain polymer and the carboxyl group of rhodamine B and the polymerization carbonization process of the two. In the low-temperature stage, the chain growth of the precursor is mainly carried out, and the intermolecular dehydration condensation process is intensified with the effective collision between molecules; then the temperature is further increased, the thermal motion is intensified, the dehydration condensation process continues and is accompanied by a partial carbonization process, and CPDs begin to appear; finally, in the constant temperature stage, as the degree of carbonization increases, the final structure of the carbon core is stably formed to obtain CPDs. In the above process, the addition of acid, the type and ratio of raw materials, and the selection of reaction temperature are very critical, and precise optimization is required to achieve the excellent effect of the present invention, and large-scale production can be achieved on this basis. In addition, the selection of precursors is diverse and functional, and the raw materials required for each step of the carbonization process are cheap, simple to operate, low cost, and the reaction conditions are easy to achieve. The preparation process and the final product are non-toxic, with a high yield (≥85%) and environmentally friendly.

[0023] 2. Rhodamine B of the present invention contains carboxyl groups but is not a classical organic acid. It is not easy to react with hydroxyl groups, amino groups, etc. Therefore, it is very necessary to add a small molecule acid catalyst during the carbonization process for the formation of carbonized polymer dots; the small molecule acid promotes the occurrence of the polycondensation process, which has a greater influence on the degree of grafting of polymer chains on the surface of CPDs, and further affects the performance of the final product, such as solid-state luminescence behavior. Rhodamine B is generally believed to be unfavorable for luminescence during the carbonization process as a dye, so it is rarely used in a pyrolysis reaction system; if Rhodamine B is used as a single carbonization precursor to prepare carbon dots through the same technical method of the present invention, the resulting carbon dots are significantly quenched in the solid state. The structure of the polyether long-chain polymer of the present invention has a greater influence on the performance of carbon dots. The polymer long chain bonded to the surface of the carbon core can effectively disperse the fluorescent chromophore, resist the ACQ effect of the luminescent material, and achieve efficient solid-state luminescence of carbon dots. It has the ability to be used as a commercial phosphor and can be used in photoluminescent devices such as LEDs.

[0024] 3. The carbonized polymer dots prepared by the method of the present invention have both high temperature resistant surface activity and solid-state luminescence performance, can emit high brightness red light, have a high photoluminescence solid quantum yield (40.04%), and have good biocompatibility, and can be dissolved in a variety of solvents of different polarities. The surface activity of the carbonized polymer dots of the present invention is better than that of general amphiphilic carbon dots and precursor Pluronic, especially the surface activity under high temperature environment, and has the advantage of high turbidity point, and has the ability to act as a surfactant, which is expected to replace some existing non-ionic surfactants to achieve high performance and visualization of related surfactants in the application field.

[0025] 4. The high cloud point advantage of the carbonized polymer dots of the present invention can be used in combination with low cloud point and high surface activity silicone surfactants to achieve synergistic effects between the two, providing a new application idea for CPDs as surfactants, which is of great significance to the petroleum industry, leather industry, printing and dyeing industry, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 Solid photos of the carbonized polymer dots prepared in Example 1 and the raw material Rhodamine B under room light (left) and 365 nm ultraviolet light (right).

[0027] Figure 2 XRD patterns of carbonized polymer dot solid powders obtained in Examples 1, 2, and 3.

[0028] Figure 3 Fluorescence emission spectra of carbonized polymer dot solid powders obtained in Examples 1, 2, and 3. The excitation wavelength is 365 nm.

[0029] Figure 4 Fluorescence spectra of carbonized polymer dot solid powders prepared in Examples 4, 5, and 6.

[0030] Figure 5 Fluorescence emission spectra of carbonized polymer dot solid powders prepared in Examples 7, 8, 9, and 10, wherein the excitation wavelength is 500 nm.

[0031] Figure 6 Fluorescence emission spectra of carbonized polymer dot solid powders prepared in Examples 1, 11, 12, 13, 14, 15, and 16, wherein the excitation wavelength is 500 nm.

[0032] Figure 7 Fluorescence emission spectra of carbonized polymer dot solid powders prepared in Examples 1, 17, 18, and 19, wherein the excitation wavelength is 500 nm.

[0033] Figure 8 Fluorescence emission spectra of carbonized polymer dot solid powders prepared in Examples 1, 20, and 21, wherein the excitation wavelength is 500 nm.

[0034] Fig. 9 Photographs of the carbonized polymer dot solids prepared in Examples 22-24 under room light (top) and 365 nm ultraviolet light (bottom).

[0035] Fig.10 Fluorescence emission spectra of carbonized polymer dot solid powders prepared in Example 1 and Comparative Examples 1-2, wherein the excitation wavelength is 500 nm, and the inset figures are photos of carbonized polymer dot solids irradiated with room light (left) and 365 nm ultraviolet light (right).

[0036] Fig.11 Fluorescence lifetime spectra of carbonized polymer dot solid powders prepared in Example 1 and Comparative Examples 1-2.

[0037] Fig.12 Fluorescence emission spectra of carbonized polymer dots prepared in Example 1 in organic solvent environments of different polarities, wherein the excitation wavelength is 500 nm and the concentration of carbonized polymer dots is 10 mg / mL.

[0038] Fig.13 Fluorescence emission spectra of the aqueous solution of carbonized polymer dots prepared in Example 1 at different excitation wavelengths.

[0039] The concentration of carbonized polymer dots was 10 mg / mL.

[0040] Fig.14 Surface activity of carbonized polymer dots prepared in Example 1 and raw material F68 in water, wherein the water temperature is 20°C.

[0041] Fig.15Comparison of the temperature-dependent surface activities of the carbonized polymer dots prepared in Example 1 and the raw material F68 in water.

[0042] Among them, the concentration is 10mg / mL.

[0043] Fig.16 The temperature-dependent surface activity comparison of carbonized polymer dots prepared in Example 1 and polyether-modified trisiloxane (PTS) in water, wherein the ratio of the two was changed to control the total concentration to be 5 mg / mL. DETAILED DESCRIPTION

[0044] In order to better understand the present invention, it is further described below in conjunction with specific embodiments.

[0045] Unless otherwise specified, the experimental methods used in the examples are conventional methods.

[0046] Unless otherwise specified, the materials and reagents used in the examples can be obtained from commercial sources.

[0047] Example 1

[0048] A method for preparing carbonized polymer dots having both high temperature resistant surface activity and solid-state luminescence, comprising the steps of:

[0049] Take 0.616g Pluronic F68 (mass average molecular weight is about 8400) in the polytetrafluoroethylene reactor lining, add 10mL water, then add 13μL hydrochloric acid aqueous solution (mass fraction 35%), and finally add 0.0154g rhodamine B (RhB), use mechanical stirring to mix evenly, add to the reactor, seal, place the reactor in an oven and heat, seal, and heat at 230°C. Heat for 2h (start timing when the temperature rises to 230°C), after the sample cools naturally to room temperature, transfer it to a 10000Da dialysis bag, the outside of the dialysis bag is deionized water, and dialyze at room temperature for 7 days. After the solution in the dialysis bag after dialysis is evaporated to remove most of the water, a concentrated solution is obtained, and the concentrated solution is freeze-dried to obtain carbonized polymer dots (F68-CPDs).

[0050] like Figure 1 The carbonized polymer dots prepared in this example have fluorescence emission capability in the solid state. As shown in the solid photos of carbonized polymer dots and rhodamine B, the carbonized polymer dots are rose red under room light and accompanied by bright red photoluminescence under ultraviolet light. In contrast, the dark green rhodamine B solid has almost no fluorescence under ultraviolet light.

[0051] Example 2

[0052] A method for preparing carbonized polymer dots with both high temperature resistant surface activity and solid-state luminescence is as described in Example 1, except that Pluronic F68 is replaced by PEG (mass average molecular weight is about 8000); other steps and conditions are consistent with Example 1.

[0053] Example 3

[0054] A method for preparing carbonized polymer dots having both high temperature resistant surface activity and solid-state luminescence, as described in Example 1, except that Pluronic F68 is replaced by Pluronic L64 (mass average molecular weight is about 2900), and the molecular weight cutoff of the dialysis bag is adjusted to 4000Da; the other steps and conditions are the same as in Example 1.

[0055] Example 4

[0056] A method for preparing carbonized polymer dots having both high temperature resistant surface activity and solid-state luminescence, comprising the steps of:

[0057] Take 0.0770g Pluronic F68 (mass average molecular weight is about 8400) in the polytetrafluoroethylene reactor lining, add 10mL water, then add 26μL hydrochloric acid aqueous solution (mass fraction 35%), and finally add 0.0154g rhodamine B, use mechanical stirring to mix evenly and add to the reactor, seal, place the reactor in an oven and heat it at 180℃. Heat for 3h (start timing when the temperature rises to 180℃), after the sample cools naturally to room temperature, transfer it to a 10000Da dialysis bag, the outside of the dialysis bag is deionized water, and dialyze at room temperature for 7 days. After the solution in the dialysis bag after dialysis is evaporated to remove most of the water, a concentrated solution is obtained, and the concentrated solution is freeze-dried to obtain carbonized polymer dots. The product yield is about 80%.

[0058] Example 5

[0059] A method for preparing carbonized polymer dots with both high temperature resistant surface activity and solid-state luminescence is as described in Example 4, except that the hydrochloric acid aqueous solution is replaced by sulfuric acid aqueous solution (mass fraction 98%); the other steps and conditions are consistent with Example 4. The product yield is about 2%.

[0060] Example 6

[0061] A method for preparing carbonized polymer dots with both high temperature resistant surface activity and solid-state luminescence is as described in Example 4, except that the hydrochloric acid aqueous solution is replaced by phosphoric acid (analytical grade); the other steps and conditions are the same as in Example 4. The product yield is about 4%.

[0062] Example 7

[0063] A method for preparing carbonized polymer dots having both high temperature resistant surface activity and solid-state luminescence, comprising the steps of:

[0064] Take 0.9240g Pluronic F68 (mass average molecular weight is about 8400) in the polytetrafluoroethylene reactor lining, add 10mL water, then add 13μL hydrochloric acid aqueous solution (mass fraction 35%), and finally add 0.0154g rhodamine B, use mechanical stirring to mix evenly and add to the reactor, seal, place the reactor in an oven and heat it at 250°C. After heating for 1.5h (start timing when the temperature rises to 250°C), after the sample is naturally cooled to room temperature, it is transferred to a 10000Da dialysis bag, and the outside of the dialysis bag is deionized water, and dialyzed at room temperature for 7 days. After the solution in the dialysis bag after dialysis is evaporated to remove most of the water, a concentrated solution is obtained, and the concentrated solution is freeze-dried to obtain carbonized polymer dots.

[0065] Example 8

[0066] A method for preparing carbonized polymer dots having both high temperature resistant surface activity and solid-state luminescence is as described in Example 7, except that the amount of hydrochloric acid aqueous solution added is adjusted to 7 μL; the other steps and conditions are consistent with Example 7, and polyether long chain modified carbonized polymer dots are obtained.

[0067] Example 9

[0068] A method for preparing carbonized polymer dots having both high temperature resistant surface activity and solid-state luminescence is as described in Example 7, except that the amount of hydrochloric acid aqueous solution added is adjusted to 26 μL; the other steps and conditions are consistent with Example 7.

[0069] Example 10

[0070] A method for preparing carbonized polymer dots having both high temperature resistant surface activity and solid-state luminescence is as described in Example 7, except that the amount of hydrochloric acid aqueous solution added is adjusted to 52 μL; the other steps and conditions are consistent with Example 7.

[0071] Embodiment 11

[0072] A method for preparing carbonized polymer dots with both high temperature resistant surface activity and solid-state luminescence is as described in Example 1, except that the amount of F68 added is adjusted to 0.0770 g; the other steps and conditions are consistent with Example 1.

[0073] Example 12

[0074] A method for preparing carbonized polymer dots with both high temperature resistant surface activity and solid-state luminescence is as described in Example 1, except that the amount of F68 added is adjusted to 0.1540 g; the other steps and conditions are consistent with Example 1.

[0075] Embodiment 13

[0076] A method for preparing carbonized polymer dots with both high temperature resistant surface activity and solid-state luminescence is as described in Example 1, except that the amount of F68 added is adjusted to 0.3080 g; the other steps and conditions are consistent with Example 1.

[0077] Embodiment 14

[0078] A method for preparing carbonized polymer dots with both high temperature resistant surface activity and solid-state luminescence is as described in Example 1, except that the amount of F68 added is adjusted to 0.4620 g; the other steps and conditions are consistent with Example 1.

[0079] Embodiment 15

[0080] A method for preparing carbonized polymer dots with both high temperature resistant surface activity and solid-state luminescence is as described in Example 1, except that the amount of F68 added is adjusted to 0.7700 g; the other steps and conditions are consistent with Example 1.

[0081] Example 16

[0082] A method for preparing carbonized polymer dots with both high temperature resistant surface activity and solid-state luminescence is as described in Example 1, except that the amount of F68 added is adjusted to 0.9240 g; the other steps and conditions are consistent with Example 1.

[0083] Embodiment 17

[0084] A method for preparing carbonized polymer dots having both high temperature resistant surface activity and solid-state luminescence is as described in Example 1, except that the amount of hydrochloric acid aqueous solution added is adjusted to 7 μL; the other steps and conditions are consistent with Example 1, and polyether long chain modified carbonized polymer dots are obtained.

[0085] Embodiment 18

[0086] A method for preparing carbonized polymer dots having both high temperature resistant surface activity and solid-state luminescence is as described in Example 1, except that the amount of hydrochloric acid aqueous solution added is adjusted to 26 μL; the other steps and conditions are consistent with Example 1.

[0087] Embodiment 19

[0088] A method for preparing carbonized polymer dots having both high temperature resistant surface activity and solid-state luminescence is as described in Example 1, except that the amount of hydrochloric acid aqueous solution added is adjusted to 52 μL; the other steps and conditions are consistent with Example 1.

[0089] Embodiment 20

[0090] A method for preparing carbonized polymer dots having both high temperature resistant surface activity and solid-state luminescence is as described in Example 1, except that the pyrolysis temperature is changed to 180°C; the other steps and conditions are consistent with Example 1.

[0091] Embodiment 21

[0092] A method for preparing carbonized polymer dots having both high temperature resistant surface activity and solid-state luminescence is as described in Example 1, except that the pyrolysis temperature is changed to 250°C; the other steps and conditions are consistent with Example 1.

[0093] Embodiment 22

[0094] A method for preparing carbonized polymer dots is as described in Example 1, except that the precursor rhodamine B is replaced with methyl blue; the other steps and conditions are consistent with Example 1.

[0095] Embodiment 23

[0096] A method for preparing carbonized polymer dots is as described in Example 1, except that the precursor rhodamine B is replaced with sodium fluorescein; the other steps and conditions are consistent with those in Example 1.

[0097] Embodiment 24

[0098] A method for preparing carbonized polymer dots is as described in Example 1, except that the precursor rhodamine B is replaced with calcein; the other steps and conditions are consistent with those in Example 1.

[0099] Comparative Example 1

[0100] A method for preparing carbonized polymer dots, as described in Example 1, except that Pluronic F68 is not added; the other steps and conditions are the same as in Example 1 (RhB-CPDs).

[0101] Comparative Example 2

[0102] A method for preparing carbonized polymer dots is as described in Example 1, except that no hydrochloric acid aqueous solution is added; the other steps and conditions are the same as in Example 1.

[0103] Test Example 1

[0104] The XRD patterns of the carbonized polymer dots prepared in Examples 1-3 are as follows: Figure 2As shown. The XRD of Example 3 shows that the carbon dots obtained from the viscous precursor L64 have a broad diffraction peak centered at a 2θ angle of 20.24°, which is attributed to the graphite carbon (002) plane, showing an amorphous state. Thanks to the good crystallization properties of the raw materials, the crystallization state of the solid powder of the samples obtained in Examples 1 and 2 is consistent with that of F68 and PEG. At 2θ angles of 18.96° and 20°, the narrow diffraction peaks show a smaller grain size. Among them, the carbonized polymer dots obtained using F68 as a precursor show clearer and more orderly crystallization behavior, which is the basis for obtaining carbon dots with excellent optical properties.

[0105] Test Example 2

[0106] The fluorescence spectra of the carbonized polymer dot solid powders prepared in Examples 1-3 are as follows: Figure 3 As shown, the fluorescence spectrum was measured at an excitation wavelength of 365 nm. Among them, the optimal excitation of the carbonized polymer dots prepared in Example 1 was 540 nm, and the optimal emission wavelength was 592 nm; the optimal excitation of the carbonized polymer dots prepared in Example 2 was 500 nm, and the optimal emission wavelength was 575 nm; the carbonized polymer dots prepared in Example 3 had no obvious red fluorescence emission. The solid-state luminescence properties of carbonized polymer dots depend on the structure of the polyether long-chain polymer itself and the number of polymer monomers, among which the side chain structure of the polymer has a great influence. Compared with the other two carbon dots, the carbonized polymer dots prepared using long-chain F68 (Example 1) have a greater steric hindrance around the chromophore due to the structural advantages of its polymer monomer polyoxypropylene, thereby exhibiting optical behaviors with stronger fluorescence and longer emission wavelengths.

[0107] Test Example 3

[0108] The fluorescence spectra of the carbonized polymer dot solid powders prepared in Examples 4-6 are as follows: Figure 4 As shown, the fluorescence spectra were measured at different excitation wavelengths. Among them, the carbonized polymer dots prepared in Example 4 had an optimal excitation wavelength of 560 nm and an optimal emission wavelength of 590 nm; the carbonized polymer dots prepared in Example 5 had an optimal excitation wavelength of 355 nm and an optimal emission wavelength of 610 nm; the carbonized polymer dots prepared in Example 6 had an optimal excitation wavelength of 365 nm, showing a double-peak emission with emission wavelengths of 425 nm and 635 nm, respectively. Compared with the other two carbon dots, the solid powder of the carbonized polymer dots prepared using hydrochloric acid (Example 4) showed the strongest fluorescence and a high product yield (~80%).

[0109] Test Example 4

[0110] The fluorescence spectra of the carbonized polymer dot solids prepared in Examples 7-10 are as follows: Figure 5As shown in the figure (excitation wavelength is 500nm), it can be seen that with the increase of hydrochloric acid addition, the solid fluorescence intensity of carbonized polymer dots first increases and then decreases, and the effect is best when the addition amount is 13μL (Example 7). This shows that a small amount of hydrochloric acid will lead to insufficient polymerization and poor cross-linking network effect of polyether surface modification; while excessive addition of hydrochloric acid as a strong acid solvent will seriously damage the precursor structure and carbonization effect.

[0111] Test Example 5

[0112] The fluorescence spectra of the carbonized polymer dot solid powders prepared in Examples 11-16 are as follows: Figure 6 As shown, the fluorescence spectrum was measured at an excitation wavelength of 500nm. The amount of precursor RhB added was fixed, and the amount of block polymer F68 added was changed. It is worth noting that with the increase of F68, the fluorescence intensity of the carbon dot solid powder first increased and then decreased, and the optimal emission wavelength was around 590nm. Compared with other precursor addition amounts, the carbonized polymer dots prepared in Example 1 showed the highest fluorescence intensity, the product yield was ~85%, and the ratio used was 1:40 (mass ratio, RhB:F68).

[0113] Test Example 6

[0114] The fluorescence spectra of the carbonized polymer dot solid powders prepared in Examples 17-19 are as follows: Figure 7 As shown (excitation wavelength is 500nm). In the early carbonization process, since the lower reaction temperature often promotes the interaction between functional groups of different precursors, they undergo a dehydration condensation process to aggregate to obtain longer polymer chains. At this time, the importance of hydrochloric acid as a catalyst is self-evident. The introduction of an appropriate amount of hydrochloric acid will promote the grafting of polymer chains on the surface of carbon dots to obtain carbonized polymer dots with the best branched structure. Similar to the conclusions obtained in Examples 7-10, compared with carbonized polymer dots with other amounts of hydrochloric acid added, the carbonized polymer dots prepared in Example 1 exhibit the best fluorescence intensity. Comparing Examples 7-10, the effect is best when the amount of precursor F68 added is 0.616g and the reaction temperature is 230°C.

[0115] Test Example 7

[0116] The fluorescence spectra of the carbonized polymer dot solid powders prepared in Examples 20-21 are as follows: Figure 8 As shown, the fluorescence spectrum was measured at an excitation wavelength of 500 nm. As the reaction temperature increased, the degree of carbonization increased, forming carbonized polymer dots with rich surface functional groups such as hydroxyl, amino, carboxyl, and carbonyl groups on the surface, and the fluorescence intensity reached a peak at a reaction temperature of 230°C.

[0117] Test Example 8

[0118] The photos of the carbonized polymer dot solid powders prepared in Examples 22-24 under (upper) room light and (lower) 365 nm ultraviolet light are shown in FIG. Fig. 9 As shown. After the rhodamine B in Example 1 was replaced with luminescent molecules such as methyl blue, sodium fluorescein, and calcein, the carbonized polymer dots emitted bright white, yellow, and red fluorescence emissions under 365nm ultraviolet light. This proves that the technology of the present invention has a universal solution strategy for achieving efficient solid-state luminescence for other ACQ molecules containing active groups.

[0119] Test Example 9

[0120] The fluorescence spectra of the carbonized polymer dot solid powders prepared in Example 1 and Comparative Examples 1-2 are as follows: Fig.10 As shown in the figure, the fluorescence emission spectrum was measured at an excitation wavelength of 500nm. Without adding F68 during the carbonization process, the obtained carbon dots were obviously quenched in the solid state, which shows the importance of the polymer precursor; without adding hydrochloric acid aqueous solution, the fluorescence intensity of the obtained carbon dots in the solid state is far less than that of the sample with an appropriate amount of hydrochloric acid aqueous solution participating in the carbonization process. Fig.11 As shown, the solid fluorescence lifetime of the carbonized polymer dots prepared in Example 1 is the highest, which can reach 3.506ns, while the solid fluorescence lifetimes of the raw material Rhodamine B and Comparative Example 1 are the shortest, 1.019ns and 0.710ns, respectively. It is proved that the electron-donating functional groups such as -OH and -NH3 provided by the precursor inhibit the non-radiative recombination of excitons and increase the fluorescence lifetime of the carbonized polymer dots. The photoluminescent solid quantum yield of the carbonized polymer dots prepared in Example 1 is 40.04%.

[0121] Test Example 10

[0122] The carbonized polymer dots prepared in Example 1 were dissolved in 9 solvents with different polarities (water, methanol, ethanol, dimethyl sulfoxide, N,N-dimethylformamide, acetone, ethyl acetate, 1,4-dioxane, toluene) and their fluorescence spectra were measured at an excitation wavelength of 500 nm. The concentration of the carbonized polymer dots was controlled to be 10 mg / mL. The results are as follows: Fig.12 As shown. As can be seen from the figure, in water, dimethyl sulfoxide, N,N-dimethylformamide, acetone, ethyl acetate, 1,4-dioxane, and toluene, the best emission of carbonized polymer dots is 580nm; in methanol and ethanol, the best emission of carbonized polymer dots is 570nm. It is worth noting that the luminescence intensity of carbonized polymer dots in solvents of different polarities is significantly different. At the same concentration, carbonized polymer dots show the strongest fluorescence emission in methanol, ethanol, and water. The photoluminescence quantum yield of the carbonized polymer dot aqueous solution (5mg / mL) is 15.37%, and the fluorescence lifetime is 3.378ns.

[0123] Test Example 11

[0124] The carbonized polymer dots prepared in Example 1 were dissolved in water and their fluorescence spectra were measured at different excitation wavelengths, wherein the concentration of the carbonized polymer dots was controlled to be 10 mg / mL. The results are as follows: Fig.13 As shown in Figure 3, it is independent of the excitation wavelength, indicating that the luminescence of CPDs comes from the luminescence of the carbon core formed during the carbonization of the precursor Rhodamine B.

[0125] Test Example 12

[0126] The carbonized polymer dots prepared in Example 1 and Pluronic F68 were dissolved in water at 20°C. Fig.14 ) and different temperatures ( Fig.15 ) was used to test the surface tension. Thanks to the appropriate reaction conditions and precursor properties, the carbonized polymer dots retained the nonionic surfactant properties of F68 and the ionic properties of RhB. The carbonized polymer dots had a high turbidity point and the surface activity was resistant to high temperatures. Figure 14-15 As shown in Figure 2, the surface activity of carbonized PDOs depends on the structure of the polyoxyethylene-polyoxypropylene long-chain polymer itself and the number of polymer monomers, among which the side chain structure of the polymer has a great influence. Specifically, the surface activity of carbonized PDOs prepared from triblock polymer F68 is better than that of polyoxyethylene-polyoxypropylene-polyoxyethylene long-chain polymer raw material (F68) at room temperature (20°C), and this result is shown in Figure 2. Fig.14 The surface tension statistics of polymer F68 and carbonized polymer dots at different temperatures were ( Fig.15 ) show the same experimental conclusion.

[0127] Test Example 13

[0128] The carbonized polymer dots prepared in Example 1 were mixed with polyether-modified trisiloxane ((C2H4O)8.C 11 H 30 O3Si3, PTS, available from Shandong Dongyue Organic Silicon Materials Co., Ltd.) were dissolved in water, the total concentration of carbonized polymer dots and PTS was controlled to be 5 mg / ml, the mass ratio of carbonized polymer dots to polyether-modified trisiloxane (PTS) in water was changed, and the surface tension statistics measured at different temperatures were as follows: Fig.16 Among them, polyether-modified trisiloxane (PTS) has a lower surface tension (cmc ~ 21.6mN / m, 1.3×10 -4 mol / L, room temperature), while the turbidity point is low (~50℃), and the carbonized polymer dots have a higher turbidity point (>100℃). The combination of the two can achieve synergistic enhancement, and the combination can achieve high turbidity point and surface activity (turbidity point>100℃, surface tension<20mN / m). Fig.16The illustration also proves the improved performance after compounding. Under the irradiation of the laser pen, a clear light path is shown, which indicates that the compounded solution is in a sol state. Therefore, carbonized polymer dots are easy to prepare and have excellent performance, and can be used as a highly efficient surfactant additive.

Claims

1. A method for preparing carbonized polymer dots having both high temperature resistant surface activity and solid-state luminescence, comprising the steps of: The precursor, polyether long-chain polymer, acid and water are mixed evenly, subjected to hydrothermal reaction, and then purified and freeze-dried to obtain carbonized polymer dots with both high temperature resistant surface activity and solid-state luminescence; the precursor is rhodamine B, methyl blue, sodium fluorescein or calcein.

2. The method for preparing carbonized polymer dots having both high temperature resistant surface activity and solid-state luminescence according to claim 1, characterized in that: The polyether long-chain polymer is Pluronic F68, Pluronic L64 or PEG; preferably, the mass average molecular weight of Pluronic F68 is 8000-9000, the mass average molecular weight of Pluronic L64 is 2000-4000, and the mass average molecular weight of PEG is 7000-9000.

3. The method for preparing carbonized polymer dots having both high temperature resistant surface activity and solid-state luminescence according to claim 1, characterized in that: The acid is a hydrochloric acid aqueous solution, a sulfuric acid aqueous solution or a phosphoric acid solution; the mass concentration of the acid is 35 to 100%.

4. The method for preparing carbonized polymer dots having both high temperature resistant surface activity and solid-state luminescence according to claim 1, characterized in that: The mass ratio of the precursor to the polyether long-chain polymer is 1:2 to 1:100, preferably 1:5 to 1:60, more preferably 1:30 to 1:50, and most preferably 1:

40.

5. The method for preparing carbonized polymer dots having both high temperature resistant surface activity and solid-state luminescence according to claim 1, characterized in that: The mass ratio of the precursor to the volume ratio of the acid is 1:0.1 to 10 g / mL, preferably 1:0.4 to 4 g / mL, preferably 1:0.8 to 0.9 g / mL, and more preferably 1:0.84 g / mL.

6. The method for preparing carbonized polymer dots having both high temperature resistant surface activity and solid-state luminescence according to claim 1, characterized in that: The mass ratio of the precursor to the volume of water is 0.001 to 1 g / mL.

7. The method for preparing carbonized polymer dots having both high temperature resistant surface activity and solid-state luminescence according to claim 1, characterized in that: The hydrothermal reaction temperature is 170 to 250° C., preferably 180 to 240° C., and more preferably 220 to 230° C.; the hydrothermal reaction time is 0.5 to 8 h, preferably 1 to 3 h, and more preferably 1.5 to 2.5 h.

8. The method for preparing carbonized polymer dots having both high temperature resistant surface activity and solid-state luminescence according to claim 1, characterized in that: The purification method is dialysis; the dialysis time is 4 to 15 days, preferably 5 to 7 days; the molecular weight cutoff of the dialysis bag used for dialysis is X+100 to X+3000Da, wherein X is the mass average molecular weight of the polyether long-chain polymer.

9. A carbonized polymer dot having both high temperature resistant surface activity and solid-state luminescence, characterized in that: Prepared by the method according to any one of claims 1 to 8.

10. The use of carbonized polymer dots having both high temperature resistant surface activity and solid-state luminescence as claimed in claim 9, characterized in that: Applied to photoluminescent devices, phosphors or as surfactants; preferably, the carbonized polymer dots can be compounded with polyether-modified trisiloxane as a surfactant, wherein the mass ratio of the carbonized polymer dots to the polyether-modified trisiloxane is 1-9:9-1, preferably 5-7:3-5.

Citation Information

Cited By

  • Carbonized polymer / cellulose nanocrystal composite material for efficient circular polarization luminescence and phosphorescence emission as well as preparation and application of carbonized polymer / cellulose nanocrystal composite material

    CN119613817A

  • A high-efficiency circularly polarized luminescence and phosphorescence emitting carbonized polymer / cellulose nanocrystal composite material and preparation and application thereof

    CN119613817B

  • High-sensitivity ellipsoidal rhodamine B-gelatin fluorescent nanometer thermometer and preparation method thereof

    CN120160723A